Exploring the Use of ChatGPT 3.5 in the Development of Rootine Website Front End - Mahardhika, Bima Julian; Putri, Tiara Ariyanto; Rudiansyah, Cahya; Fami, Amata; Barus, Irma R.G (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This study aims to investigate and assess the capabilities of ChatGPT. This chatbot communicates with people using artificial intelligence (AI) and can help with various activities. This study looks at how ChatGPT may help with the front-end development of the Rootine farmer helper website for Trinity Company. Through qualitative descriptive methodologies and practical investigation of ChatGPT, this study discovered that ChatGPT's response time to requests may have been enhanced. This is because the version of ChatGPT AI being used, the requirement for more user comprehension in request delivery, and restrictions on replying to requests based on the outcomes of prior answers are the causes of this. This study is anticipated to add to the most recent research on ChatGPT's capacity to assist front-end development.